Approach for self-optimising assembly of optical systems. Issue 11 (1st November 2016) - Holters, Martin; Gatej, Alexander; Haag, Sebastian; Müller, Tobias; Loosen, Peter; Brecher, Christian
Abstract : The alignment of optical components is challenging. This paper proposes self-optimisation as a means for reducing planning efforts and increasing the system's autonomy. Hence, reduced costs and production times can be achieved. Moreover, self-optimising approaches for laser optics assembly enabling autonomous compensation of manufacturing tolerances are presented. Based on ray-tracing simulation, the assembly system carries out the alignment of optics automatically. During the alignment process the laser beam is monitored and analysed. The ray-tracing simulation is updated in a closed-loop manner for gaining information on required correction movements. This information is passed to the assembly system in order to achieve a valid optical function using tolerance-affected components. The choice of metrology as well as the interfaces between different software packages and hardware components will be discussed. The alignment procedure will be described using the example of a miniaturised optical system suitable for laser beam guiding and shaping.